Scrupocellaria (Bryozoa: Cheilostomata) from the Queensland coast, with the description of three new species - Tilbrook, Kevin J.; Vieira, Leandro M. (Zootaxa, 2012)
Among the Scrupocellaria species previously reported from Queensland, three are here redescribed — S. cervicornis, S.curvata and S. diadema; two other species, S. frondis and S. sinuosa, are recorded from the area for the first time; threenew species, S. hamata n. sp., S. prolata n. sp. and S. peltata n. sp., are also described, and the remainder are discussed.The need for the re-examination of specimens assigned to this genus is highlighted. The geographic range of some Scrupocellaria species is far more limited than once thought.